Pengembangan E-Modul Berbasis Komik dilengkapi Video Faktual pada Pelajaran IPA SMP Kelas VII: (The Development of Comic-Based E-Modules with Factual Videos in Science Lessons in Class VII SMP) - Humairah Farsa; Asni Johari; Kamid Kamid (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2022)
Technology-based teaching materials were developed to assist student learning activities. The use of teaching materials that can be used in the form of e-modules is one of the teaching materials that can help students to learn. In order for e-modules to be attractive to students, it is necessary to develop more attention to student interests. This study aims to produce comic-based e-modules equipped with factual videos for class VII science lessons on environmental pollution, global warming and the earth's layers. This research is a development research that adapts the ADDIE development model. The ADDIE model development stage consists of analysis, design, development, implementation and Evolution. The stage before testing the e-module is validated first. Validation consists of material validation and media validation. The validation of the very category material and the very good category of media validation, so that the e-module was declared worthy to be tested. The e-module was piloted at SMP IT Nurul Ilmi Jambi class VII. Based on the results of the study, it was concluded that the comic-shaped module equipped with factual videos in the seventh grade science lesson was declared effective. Key words: E-Module, Comic Based, Factual Video Abstrak Bahan ajar berbasis teknologi dikembangkan untuk memebantu kegiatan belajar siswa. Penggunaan bahan ajar yang dapat digunakan berupa e-modul merupakan salah satu bahan ajar yang dapat membantu siswa untuk belajar. Agar e-modul yang menarik bagi siswa maka perlu pengembangan yang lebih memperhatikan minat siswa. Penelitian ini bertujuan utuk menghasilkan e-modul berbasis komik dilengkapi video faktual untuk pelajaran IPA kelas VII pada materi pencemaran lingkungan, pemanasan global dan lapisan bumi. Penelitian ini merupakan penelitian pengembangan yang mengadaptasikan model pengembangan ADDIE. Tahap pengembangan model ADDIE Terdiri dari analysis, design, development, implementation dan Evolution. Tahap sebelum diujicobakan e-modul divalidasi terlebih dahulu. Validasi terdiri dari validasi materi dan validasi media. Validasi materi kategori sangat dan validasi media kategori sangat baik, sehingga e-modul dinyatakan layak untuk diujicobakan. E-modul diujicobakan di SMP IT Nurul Ilmi Jambi kelas VII. Berdasarkan hasil penelitian disimpulkan bahwa modul berbentuk komik dilengkapi video faktual pada pelajaran IPA kelas VII dinyatakan efektif. Kata kunci:E-modul, Berbasis komik, Video faktual